2019
DOI: 10.1073/pnas.1904813116
|View full text |Cite
|
Sign up to set email alerts
|

Effective concentrations enforced by intrinsically disordered linkers are governed by polymer physics

Abstract: Many multidomain proteins contain disordered linkers that regulate interdomain contacts, and thus the effective concentrations that govern intramolecular reactions. Effective concentrations are rarely measured experimentally, and therefore little is known about how they relate to linker architecture. We have directly measured the effective concentrations enforced by disordered protein linkers using a fluorescent biosensor. We show that effective concentrations follow simple geometric models based on polymer ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
142
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 57 publications
18
142
1
Order By: Relevance
“…A key idea behind this model is that we assume that the longer linker in CaMKII-b slows down the rates of trans-phosphorylation reactions within a holoenzyme when compared to CaMKII-Page 12 of 55 a, but that the rates of cis-phosphorylation are the same as in the two isoforms (Sørensen and Kjaergaard, 2019).…”
Section: Camkii-b With a Long Kinase-hub Linker Acquires Inhibitorymentioning
confidence: 99%
“…A key idea behind this model is that we assume that the longer linker in CaMKII-b slows down the rates of trans-phosphorylation reactions within a holoenzyme when compared to CaMKII-Page 12 of 55 a, but that the rates of cis-phosphorylation are the same as in the two isoforms (Sørensen and Kjaergaard, 2019).…”
Section: Camkii-b With a Long Kinase-hub Linker Acquires Inhibitorymentioning
confidence: 99%
“…Recently, we developed a biosensor that allows measurement of intra-molecular effective concentrations. 15 We adapted this system by introducing mClover3 N-terminally in A/P and mRuby3 26 compete with the intra-molecular complex and force ring opening. To allow the free peptide to compete efficiently, we introduced a mutation in the ACTR domain of A/P (L17A) to weaken the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that the sequence of such www.biophysics.dk -9 -linkers has a large effect on effective concentrations due to attractive or repulsive interactions. 15 Linker-linker interactions may play important roles in multivalent disordered proteins, but such interactions are undesirable for the purpose of establishing a theoretical baseline. Ideally, we want linkers that solely act as tunable entropic spacers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations